Incendiary - Córdova, Zoraida (Little, Brown and Company, 2021)
"Renata was only a child when she was kidnapped and brought to the luxurious palace of Andalucía. As a memory thief, the rarest and most feared of the magical Moria, she was used by the king to carry out the deaths of thousands of her own people. Now Renata is one of the Whispers, rebel spies fighting back. The Whispers may have rescued Renata years ago, but she cannot escape their mistrust and hatred--or the overpowering memories of souls she drained during her time in the palace. When Dez, the commander of her unit--and the boy she's grown to love--is taken captive, Renata must return to Andalucía and complete Dez's top secret mission herself. but as she wades through the politics of the royal court, Renata uncovers a secret in her past that could change the fate of the entire kingdom--and end the war that has cost her everything."--Back cover.